PESAN DAKWAH GUS MIFTAH DALAM PERNIKAHAN ATTA-AUREL - Anjani, Eka; Djoyo Budiono, Tri (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2021)
A wedding sermon is essential in walimatul ursy (wedding reception) because it contains valuable marital messages for building a family based on Islamic values, for not only the couple but also the ones attending the occasion. Meanwhile, some different comprehensions about building a family may occur, including husband and wife roles in a family or decision for taking polygamy or monogamy. This paper aims to describe Gus Miftah’s da’wah messages during Atta and Aurel’s wedding sermon. It uses qualitative descriptive method, literature review as data-collecting method, and Teun A. Van Dijk’s discourse analysis as analytical method. In its macrostructure analysis, a husband should maintain his household to reach tranquillity. Some ways to settle domestic affairs are by giving in to each other, accepting strength and shortcomings and forgiving one another. Those messages are delivered in an arrangement of introduction, content and closing remarks. In its microstructure analysis, a husband should venerate his wife by providing a basic subsistence and respecting her opinion in taking a decision. Gus Miftah emphasizes background of meaning more than its detail, syntactic aspect for coherent causality, and usages of statements, interrogatives, and imperatives. And he also uses intonation and metaphor as means of delivery.